2019
DOI: 10.1038/s41419-019-1426-3
|View full text |Cite
|
Sign up to set email alerts
|

Confounding off-target effects of BH3 mimetics at commonly used concentrations: MIM1, UMI-77, and A-1210477

Abstract: Targeting anti-apoptotic BCL2 family proteins has become an attractive therapeutic strategy for many cancers, and the BCL2-selective inhibitor ABT-199 (venetoclax) has obtained clinical success. However, MCL1 can promote drug resistance and overall cancer cell survival. Thus, there is a critical need to develop an effective drug that antagonizes MCL1. However, most putative MCL1 inhibitors have been misclassified as they fail to directly inhibit MCL1 in cells, but rather induce the pro-apoptotic protein NOXA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…While many of the putative BH3 mimetics were shown to induce NOXA in leukemia and lymphoma cell lines, it was unknown whether these compounds would induce NOXA in carcinoma cell lines, or which compound is the most potent. We chose three mimetics whose mechanisms of NOXA induction were established by our laboratory: AT101, S1 and UMI-77 [ 18 , 20 , 25 ]. In addition, we have shown that microtubule-disrupting agents can also induce NOXA, and used BNC105 as a representative agent [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While many of the putative BH3 mimetics were shown to induce NOXA in leukemia and lymphoma cell lines, it was unknown whether these compounds would induce NOXA in carcinoma cell lines, or which compound is the most potent. We chose three mimetics whose mechanisms of NOXA induction were established by our laboratory: AT101, S1 and UMI-77 [ 18 , 20 , 25 ]. In addition, we have shown that microtubule-disrupting agents can also induce NOXA, and used BNC105 as a representative agent [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…AT101 alone induced little apoptosis in any of the cell lines despite induction of NOXA ( Figure 1 A). We and others have shown that NOXA-inducing compounds can sensitize cancer cells to other compounds, such as inhibitors of BCL2 and BCL-XL [ 18 , 33 , 34 ]. We sought to determine whether AT101 could sensitize carcinoma cells to other BH3 mimetics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When apoptosis is triggered, Bax moves to the mitochondrial outer membrane to promote the opening of the permeability transition (PT) pore. Sequentially, cytochrome C will be released to the cytoplasm and further activates the caspase cascade to induce apoptosis [13]. Here through western blotting, it was demonstrated that silibinin treatment would reduce the expression of Bax, cleaved caspase-3 and cleaved caspase-9, while it upregulated the expression of Bcl2 (Figure 2).…”
Section: Silibinin Regulates Apoptosis-related Protein Expressions Inmentioning
confidence: 92%